Hubungan Komitmen Organisasi dengan Kinerja pada Guru Pendidik Khusus Honorer (GPK) di Kota Padang - Riris Wisuda Tumanggor; Krisnova Nastasia (Psyche 165 Journal, 2019)
This research was conducted on Inclusive Special Educator Teachers (GPK) in Padang City. The purpose of this study was to determine the relationship between Organizational Commitment and the work performance of Inclusive Honorer (GPK) Teachers in Padang City. The sample selection technique in this study uses saturated sampling which is the method of determining the sample if the population is relatively small, less than 30 people, or research that wants to generalize with a very small error Sugiyono (2017). The sample in this study amounted to 86 people. Validity and reliability test using Cronbach Alpha.The test results show the validity coefficient on the Organizational commitment scale 0.408 to 0.695 while the reliability coefficient is 0.982. The test results of the performance scale validity coefficient showed from 0.343 to 0.682 with a reliability coefficient of 0.948. Hypothesis test results show the magnitude of the correlation coefficient of 0.487 with a significant level of p = 0,000. It means that it can be concluded that there is a significant relationship between organizational commitment and performance. Positive values indicate that the higher the organizational commitment, the higher the teacher's performance, and vice versa, the lower the organizational commitment, the lower the performance of Teachers of Special Education Teachers (GPK). The effective contribution of the compensation variable to job satisfaction is 49%